Guest

prove 1/(seca-tana)-1/cosa=1/cosa-1/(seca+tana)

prove


1/(seca-tana)-1/cosa=1/cosa-1/(seca+tana)

Grade:

1 Answers

Askiitians_Expert Yagyadutt
askIITians Faculty 74 Points
11 years ago

Hello krishna !

 

Make a bit change in the question ...shift the cos term in RHS ..

 

1/(seca-tana) + 1/(seca+tana) = 2/cosa

 

LHS

 

1/(seca-tana) + 1/(seca+tana)

 

= 2seca / (sec^2a - tan^2a)

= 2.seca  or 2/cosa ( hence proved ...)

 

Regards

 

Yagya

askiitians_expert

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free